PENGARUH PUPUK ORGANIK CAIR AIR KELAPA DAN KALIUM TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Ardian, Ardian; Syafrinal, Syafrinal; Nurbaiti, Nurbaiti; Sri Yoseva; Wulandari, Chicha (Jurnal Pertanian Agros, 2025)
Shallots (Allium ascalonicum L.) are an important horticultural commodity used as a cooking spice and medicinal raw material (Kuswardhani, 2016). Shallot production in Riau fluctuates with a decrease in 2022 and an increase in 2023, still far from community needs. Riau has variable fertility and is low in organic matter, so increasing land productivity is very important. One solution is the use of liquid organic fertilizer (POC) from coconut water waste, which can improve the physical, chemical and biological properties of the soil. The addition of inorganic fertilizer, especially potassium, is also needed to increase nutrient availability, which plays an important role in photosynthesis and tuber growth. This research aims to determine the effect of the interaction of POC coconut water and KCl fertilizer and to obtain the best treatment combination on the growth and production of shallots. The design used was a completely randomized design (CRD) with two factors: POC of coconut water (without, 200, 250 and 300 ml.l-1) and KCl dose (100, 150 and 200 kg.ha-1). There were 12 treatment combinations repeated three times, resulting in 36 experimental units. The results of the research showed that the combination of 300 ml.l-1 POC coconut water and 200 kg.ha-1 KCl fertilizer significantly increased plant height, number of leaves, harvest age, number of tubers per cluster, tuber diameter, fresh tuber weight per plant and storable tuber weight per plot.